Representasi Ijab Dan Qabul yang diwakilkan Dalam Kitab An- Nikah Karya Muhammad Arsyad Al- Banjari - Hayati, Fauziah; Ayu Dwi Lestari, Niken; Khaikannor, Nabila (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
ABSTRACT Marriage is one of the pillars of Islam which has an important role in human life. One of the conditions for a valid marriage is to have consent and qabul. Under certain conditions, consent and qabul can be delegated to other people. This research aims to analyze the representation of consent and qabul represented in the book An-Nikah by Muhammad Arsyad al-Banjari using empirical research methods, using data collection techniques, namely literature studies that examine literature reviews, journals, and marriage books by Muhammad Arsyad Al-Banjari. With this research, it is the author's great hope for the people who read this article that the application of the knowledge that the author has written can have implications in everyday life, especially in the implementation of consent to marriage. Keywords: Marriage, Consent, Represented. ABSTRAK Pernikahan merupakan salah satu rukun Islam yang memiliki peran penting dalam kehidupan manusia. Salah satu syarat sah pernikahan adalah adanya ijab dan qabul. Dalam kondisi tertentu, ijab dan qabul dapat diwakilkan kepada orang lain. Penelitian ini bertujuan untuk menganalisis representasi ijab qabul diwakilkan dalam kitab An-Nikah karya Muhammad Arsyad al-Banjari dengan menggunakan metode penelitian empiris, dengan menggunakan Teknik pengumpulan data yaitu studi pustaka yang menelaah literatur review, jurnal, serta kitab nikah karya Muhammad Arsyad Al-Banjari. Dengan adanya penelitian ini, besar harapan penulis kepada masyarakat yang membaca tulisan ini agar kiranya menerapkan ilu yang telah penulis tulis dapat diimplikasikan dalam kehidupan sehari hari terkhusus pada pelaksanaan ijab qabul dalam pernikahan. Kata Kunci: Pernikahan, Ijab Qabul, Diwakilkan.